Wittgenstein : rethinking the inner - Johnston, Paul, 1962- (Routledge, 1993)
This is a comprehensive account of Wittgenstein's work on the subject and presents a forceful challe nge to contemporary views. Written in a non-techni cal style, it throws new light on Wittgenstein's work on the problem of the Inner self.